On a New Extension of Mulholland’s Inequality in the Whole Plane - Bicheng Yang; Yanru Zhong; Qiang Chen (Journal of Function Spaces)
A new, more accurate extension of Mulholland’s inequality in the whole plane with a best possible constant factor is presented by introducing independent parameters, applying weight coefficients and using Hermite-Hadamard’s inequality. Moreover, the equivalent forms, some particular cases, and the operator expressions are considered.